ナンキョク ミズホ コウゲン デ サイシュ サレタ 1M シンセキセツ コアー ノ ケッショウ シュジク ホウイ ブンプ カイセキ - 中尾, 正義; ナカオ, マサヨシ; NAKAWO, Masayoshi (国立極地研究所, 1975)
P(論文) 南極大陸みすぼ高原の「S100」地点(南緯69°38.1',東径42°51',標高1,630m)から採取された深さ1mの積雪コアについて雪の結晶c軸方位分布を測定した.方位分布図を作成するとともに「鉛直集中度」を定義し,深さに対するその変化を調べた.表面近くではc軸の卓越方位は水平方向であるが,それが,鉛直方向,水平方向と,周期的に変化しながら次第に鉛直方向集中の傾向か強まっている.上記の周期変動は霜ざらめ層あるいは年層とかなり良い一致を示している. Petrofabric analyses were carried out on a snow core from the surface to a depth of one meter obtained at S100 (69°38.1'S; 42°51'E; 1,630m above sea level) in Mizuho Plateau, East Antarctica. In order that the distribution of c-axes of snow crystals was examined, the concept of the value of X^2 was introduced and "the degree of vertical c-axis concentration" was defined. Although the predominance is in the horizontal direction as regards the degree of c-axis concentration in snow layers near the surface, this predominance periodically alternates between the horizontal and the vertical direction as the depth increases, gradually strengthening a trend for the increasing degree of vertical c-axis concentration. This periodicity shows a fairly good correlation with the positions of autumn layers or depth-hoar layers. departmental bulletin paper